2019
DOI: 10.4103/ijpsym.ijpsym_342_18
|View full text |Cite
|
Sign up to set email alerts
|

Change in Attitude among Nursing Undergraduate Students Following One-Month Exposure in a Mental Healthcare Setting

Abstract: Background:Attitude of treating professionals plays an important role in the treatment of mental illnesses. Nursing professionals are an important part of the mental health care team. As a part of their nursing coursework, nursing students are posted in a mental health setting. It is important to assess the impact of such postings on their attitudes.Materials and Methods:A total of 235 undergraduate nursing students posted in a mental healthcare setting for one month participated in the study. Their attitude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…On top of that, social media tends to use negative views toward people with mental illness. It has led to social distance toward mental illness persons (Grover et al, 2019). Furthermore, more than 150 articles regarding mental health use a negative tone, and 18.5% are associated with violence (Bakar et al, 2019;DuPont-Reyes et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…On top of that, social media tends to use negative views toward people with mental illness. It has led to social distance toward mental illness persons (Grover et al, 2019). Furthermore, more than 150 articles regarding mental health use a negative tone, and 18.5% are associated with violence (Bakar et al, 2019;DuPont-Reyes et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Grover Naveen, Jameel Sayma, Dhiman Vishal have shown that there are minor changes in attitudes towards work and towards patients in medical college students during their professional practice in a psychiatric clinic. The authors conclude that a temporary change in professional status has led to positive shifts in attitudes towards patients with mental disorders and psychiatry [33]. Excessive employment and unemployment also have a relationship with status assessments and socio-psychological attitudes.…”
Section: Itse-2020mentioning
confidence: 93%
“…Selain itu, media sosial cenderung menggunakan pandangan negatif terhadap pesakit mental. Ia telah membawa kepada penjarakan sosial terhadap pesakit mental (Grover et al, 2019). Tambahan pula, lebih daripada 150 artikel mengenai kesihatan mental menggunakan nada negatif dan 18.5% dikaitkan dengan keganasan (Bakar et al, 2019;DuPont-Reyes et al, 2020) dan lebih banyak daripada pesakit mental berbanding pesakit fizikal (22.5%: 19.7%).…”
Section: Perbincanganunclassified